Indonesian Society of Gynecologic Oncology Cancer Registration Information System: 10 Years of Implementation, Challenge, and Future - Tricia Dewi Anggraeni; Hari Nugroho; Ali Budi Harsono; Tofan Widya Utami; Brahmana Askandar Tjokroprawiro (JCO Global Oncology)
PURPOSEIndonesia still faces high disease burden from cancer and needs valid gynecologic cancer epidemiology data. The Indonesian Society of Gynecologic Oncology (INASGO) established a web-based gynecologic cancer registry. This research aims to observe and report the situation of INASGO cancer registration information system from 2011 to 2021 and provide the most recent data.METHODSThis is a quality assurance research using nonexperimental design and did not perform data manipulation. This study will evaluate comparability, validity, and completeness of cancer registry data. Information was obtained by registration files, direct observation, and interviewing cancer registry supervisors in Cipto Mangunkusumo Hospital, Jakarta.RESULTSThis cancer registry coded its data according to international standards with many participants and large cases registered. A total of 28,692 cases were reported to the cancer registry. Cervical cancer ranked highest (68.6%) with stage III being the most common found. The most frequent age group at diagnosis is 36-55 years. The most valid basic diagnostic of gynecologic cancer is histology of primary malignancy. The main challenge of the INASGO cancer registry is the lack of data validity and completeness because of poor coordination and financial support.CONCLUSIONINASGO cancer registration information system has good prospects to provide data information of patients with gynecologic cancer in policy or research matters. Poor coordination and limited financial support have to be anticipated for the sake of this cancer registry existence in the future.